2017
DOI: 10.28978/nesciences.369527
|View full text |Cite
|
Sign up to set email alerts
|

Length-Weight Relationships of Four Lessepsian Puffer Fish Specıes From Muğla Coasts of Turkey

Abstract: In this study, length-weight relationships were given belonging to Tetraodontidae family: Lagocephalus sceleratus (Gmelin, 1789), Lagocephalus spadiceus (Richardson, 1845), Lagocephalus suezensis Clark & Gohar, 1953 and Torquigener flavimaculosus Hardy & Randall, 1983. Specimens were collected via different fishing activities (e.g. longline, trammel net, bottomtrawl) from Muğla coasts (South Aegean Sea, Turkey) during 2014. Specimens were thown back sea after length and weight measurements because of restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The L-W relationship of L. sceleratus was in line with the results of other studies in the eastern Mediterranean (Kalogirou, 2013;Boustany et al, 2015;Farrag et al, 2015); however, Başusta et al (2013a) found L. sceleratus with a b value in Iskenderun Bay lower than our findings and the findings by Aydın (2011) in the Gulf of Antalya. Furthermore, Bilge et al (2017) estimated negative allometric growths for four common pufferfish species along the coasts of Muğla, adjacent to the present study area.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The L-W relationship of L. sceleratus was in line with the results of other studies in the eastern Mediterranean (Kalogirou, 2013;Boustany et al, 2015;Farrag et al, 2015); however, Başusta et al (2013a) found L. sceleratus with a b value in Iskenderun Bay lower than our findings and the findings by Aydın (2011) in the Gulf of Antalya. Furthermore, Bilge et al (2017) estimated negative allometric growths for four common pufferfish species along the coasts of Muğla, adjacent to the present study area.…”
Section: Discussionmentioning
confidence: 94%
“…Early studies on pufferfish focused mainly on initial reports on their first records (Bilecenoglu et al, 2006;Tuncer et al, 2008;Koç et al, 2011;Turan & Yağlıoğlu, 2011;Irmak & Altinağaç, 2015;Akyol & Aydın, 2016Çelik et al, 2018), length-weight relationships (Başusta et al, 2013a,b;Bilge et al, 2017), population growth (Aydın, 2011;Farrag et al, 2015), and biological parameters (Boustany et al, 2015) of a single species when studying the spatio-temporal distribution of the pufferfish (Kalogirou, 2013;Farrag et al, 2015;El-Haweet et al, 2016;Özbek et al, 2017). Kalogirou et al (2010Kalogirou et al ( , 2012 studied relationships between Posidonia spp.…”
Section: Introductionmentioning
confidence: 99%
“…Erguden et al (2015) reported negative growth (b=2.970) in their study conducted in Iskenderun Bay. Similarly, Bilge et al (2017) stated negative allometric growth (b=2.836) from the Mugla coast. However, Ayas et al (2019) reported positive allometric growth (3.326) from Mersin Bay.…”
Section: Discussionmentioning
confidence: 98%
“…To date, length-weight relationship studies have been reported very scarcely for the pufferfish species (Erguden et al, 2015;Bilge et al, 2017;Ayas et al, 2019). Besides, LWRs and condition factors according to sexes for T. flavimaculosus have not been reported from the Eastern Mediterranean.…”
Section: Introductionmentioning
confidence: 99%
“…Length-weight relationship (LWR) for the genus Lagocephalus has been reported by many researchers from India and abroad (Naik and Jalihal, 1998;Joshi, 2004;Simon and Mazlan, 2008;Başusta et al, 2013;Sirisha and Rao, 2013;Bilge et al, 2017;Padmavathi et al, 2017;Anju et al, 2019). Limited studies on the biology of L. inermis are available from India (Joshi, 2004;Padmavathi et al, 2017;Anju et al, 2019).…”
Section: Introductionmentioning
confidence: 99%